Instant porridge from natural local resources (orange sweet potato, carrot, and red bean) with highly nutritious as an alternative food source. Issue 1 (November 2021) - Putra, A; Nurminah, M; Ginting, S
Abstract: Instant porridge is one of the food product that does not require a long time to serve. Instant porridge is usually made from rice flour. Food diversification is needed to make instant porridge more nutritious, one of which is making instant porridge from natural local ingredients such as orange sweet potato, carrot, and red bean. We made the composite flour that use to make instant porridge from mixture of orange sweet potato, carrot and red bean (orange sweet potato flour : carrot flour : red bean flour), namely P1 = 80% : 15% : 5%; P2 = 70% : 20% : 10%; P3 = 60% : 25% : 15%; P4 = 50% : 30% : 20%; P5 = 40% : 35% : 25%; P6 = 30% : 40% : 30%; P7 = 20% : 45% : 35%. The finalt result showed that the formulation composite flour in P7 = 20% orange sweet potato flour : 45% carrot flour: 35% bean flour was the best formulation and produce a good instant porridge by de-Garmo method.